2000
DOI: 10.1111/j.1540-8159.2000.tb00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation from the Left Sinus of Valsalva in a Patient with Idiopathic Ventricular Tachycardia

Abstract: We report the case of a 54-year-old woman with idiopathic VT originating in the left ventricular outflow tract. She initially presented with palpitations and light-headedness. The morphology of the PVCs exhibited an inferior axis and tall R waves were noted in all the precordial leads. Spontaneous PVCs were transiently terminated by an intravenous injection of adenosine triphosphate. Radiofrequency catheter ablation from the left sinus of Valsalva successfully abolished the PVCs and the VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…A subgroup of OT VTs originate from the aortic sinuses or the main stem of the PA 7–18 . The origin of these VTs might be from the ventricular tissue supporting the base of the great arteries or the VMEs in continuity with the ventricular tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A subgroup of OT VTs originate from the aortic sinuses or the main stem of the PA 7–18 . The origin of these VTs might be from the ventricular tissue supporting the base of the great arteries or the VMEs in continuity with the ventricular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…VTs from the RVOT and LVOT share similar electrophysiological and clinical presentations, and therefore they are collectively referred to as outflow tract (OT) VT 1–6 . It has recently been shown that a subgroup of OT VTs originate from the aortic sinuses or the main stem of the pulmonary artery 7–18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual CTI conduction, suggested by lack of parallel CTI double potentials, was found in 12–18% of patients despite apparent CTI block as assessed by atrial activation sequence [33]. On the other hand, in a randomized study, analysis of double CTI potentials was not optimally correlated to the standard technique, and was considered less reliable than the classical activation mapping because of ambiguity in electrogram interpretation in one-third of cases, although it was not inferior and was helpful in difficult cases [6].…”
Section: Discussionmentioning
confidence: 99%
“…Residual slow CTI conduction has been observed in 15% of cases [50] and correlates to high recurrence rates [33], although some authors suggest that incomplete or doubtful CTI block is not clinically relevant [51]. Detection of persistent CTI conduction can also be improved by using multipolar catheters positioned along the CTI floor.…”
Section: Limitationsmentioning
confidence: 99%